Experimental studies of the phase separation mechanism in Ti-15at%A1 - Liew, H; Smith, G; Cerezo, A; Larson, D (1999)
The phase decomposition mechanism operating in a binary Ti-Al alloy in the two-phase alpha + alpha(2) region has been investigated. A Ti-15at%Al alloy was aged in the range 550-750 degrees C for various times to produce material at different stages of phase separation. The resulting microstructures have been examined experimentally using three-dimensional atom probe field ion microscopy and neutron diffraction. Results indicate that significant ordering occurs in the system prior to the onset of chemical phase separation which occurs via a spinodal reaction. The mechanism is believed to lie in the class of 'conditional spinodal' mechanisms in which one stage of the phase separation process is thermodynamically contingent upon another. (C) 1999 Elsevier Science S.A. All rights reserved.